Behind the Scenes of the Matchmaking Between Private For-Profit Sector and Cultural and Creative Sectors During Pandemic. Added Value, Motivations, and Companies’ Benefits to Join the Portugal #Entraemcena Platform. - Foà, C.; Godinho, C. (IMPERATIVE: SOCIOPOLITICAL CHALLENGES OF STRATEGIC AND ORGANISATIONAL COMMUNICATION - ECREA OSC 2023 conference, 2023)
BEHIND THE SCENES OF THE MATCHMAKING BETWEEN PRIVATE FOR-PROFIT SECTOR AND CULTURAL AND CREATIVE SECTORS DURING PANDEMIC. ADDED VALUE, MOTIVATIONS, AND COMPANIES’ BENEFITS TO JOIN THE PORTUGAL #ENTRAEMCENA PLATFORM ECREA OSC 2023 conference